What is Netflix playing at? Content convergence through video games in its multi-stage strategy - Gómez-García, Salvador (2022)
Netflix's decision to add games to its traditional content catalogue in November 2021 is perceived as a bet whose realisation is still uncertain. This study examines the first months of this new service from the company and seeks to find out how this content has been integrated into the platform, what kind of entertainment is offered and how it fits into the company's strategy, as well as how it has been received by users and subscribers. The methodology is based on a quantitative and qualitative triangulation of methods collected in an analysis sheet for each of the games in the sample (n=14). The results reflect that in these first months, the games offered are aimed to provide light entertainment and reinforce the value of the Netflix subscription, even if the games are gradually oriented towards a transmedia logic or serve to reinforce other content on the platform. In addition, the new data Netflix receives from its subscribers when they view content on the platform and their interaction with the new content could be an important asset for the future of the company.